Weighted boundedness of multilinear pseudo-differential operators - Chen, Dazhao (AIMS mathematics, 2021)
In this paper, the weighted boundedness for some multilinear operators generated by the pseudo-differential operators and the weighted Lipschitz functions are obtained.